MDR BACTERIAL INFECTIONS IN CRITICALLY ILL COVID-19 PATIENTS IN A TERTIARY CARE HOSPITAL (OF PAKISTAN) - Tayyab, Nadia; Furqan, Warda; Nasrullah, Amnah; Usman, Javaid; Ali, Sakhawat; Khan, Asad Zaman (Pakistan Armed Forces Medical Journal, 2021)
Objective: To identify antimicrobial susceptibility pattern of multidrug resistant bacteria causing secondary infections in COVID-19 patients in ICU’ sofa tertiary care hospital. Study Design: Cross–sectional study. Place and Duration of Study: Department of Microbiology, Pak Emirates Military Hospital, Rawalpindi, from Apr to Jul 2020. Methodology: This study included blood samples and endotracheal aspirates from 114 critically ill COVID-19 patients. Peripheral blood specimens were collected fromthe patients with secondary bacterial blood stream infections and endotracheal aspirates were collected from patients with ventilator associated pneumonia for culture and sensitivity. The results were interpreted according to Clinical & Laboratory Standard Institute (CLSI) 2020. Results: A total of 114 COVID-19 patients were admitted in ICU during that time period. Fourteen (12.28%) were female and 100 (87.71%) were male, age distribution was between 36-82 years. Sixty six paired blood samples were sent to the microbiology lab out of which 51 (77.2%) showed bacterial growth while 15 (22.7%) samples were negative. Out of 50 endotracheal aspirates, 42 showed bacterial growth (84%) and 8 samples did not show any significant bacterial growth (16%). Most of the endotracheal aspirates showed growth of >1 bacterial isolates. The most common gram-negative organisms were Acinetobacter baumannii (n=54) and Klebsiella pneumonia (n=26) and most common gram-positive organism isolated was Enterococcus faecium (n=9). All isolated organisms were multidrug resistant. Conclusion: Poor antimicrobial stewardship particularly in critical care units resulted in secondary bacterial infections in COVID-19 patients. The pathogens isolated were multidrug resistant including Acinetobacter baumannii, Klebsiella pneumonia and Enterococcus faecium.